Women in Physics in Zimbabwe - Danga, Helga; Tunhuma, Shandirai Malven; Gora, V.E.; Chawanda, A. (American Institute of Physics Inc., 2021)
This paper reports on the state of women in physics in Zimbabwe since 2002. Three universities have physics departments: the University of Zimbabwe, National University of Science and Technology, and Midlands State University. These institutions are all state owned. A 10-year survey shows a limited female enrollment at the undergraduate level. We report on the challenges faced by women in physics starting from the primary level of education due to culture and custom. Another reason is the lack of resources owing to the economic hardships currently experienced in the country. The authors suggest possible solutions to the current shortage of women in physics and in science in general.